Seamless engagement with tablet computers - Gabarre, Cecile; Gabarre, Serge; Din, Rosseni (Institute for Innovative Learning, Mahidol University, 2015)
The present action research sought to immerse foreign language learners in the target language and culture by seamlessly extending exposure to the language course beyond the classroom. A flipped classroom approach involving task-based and social networking learning with tablet computers was designed to engage the learners before, during and after the lessons. The flipped mobile classroom design was implemented over four semesters with a single cohort of 24 undergraduate students majoring in French in a Malaysian public university. The flipped mobile classroom aimed to instil self-regulated learning processes by providing a three dimensional scaffolding structure including seamless instructor, peer and technological support. Grounded theory’s iterative data collection and analysis procedures ensured the responsiveness and the fitness of the action plan throughout the intervention. Each lesson was taught and analysed as a micro-cycle. The instruments consisted of observations, interviews as well as self-reflexive logs and memos. The analysis included a three-level coding procedure and the constant comparative analysis of instructor as well as students’ perceptions of events. Findings revealed the appropriateness of tablet computers for catering to self-regulated learning due to the devices’ personalised, unified and flexible capacities. The Facebook social networking site hosting the flipped classroom was found to ubiquitously and efficiently support task-based learning with tablet computers. The mobile flipped classroom promoted the students’ seamless engagement and exposure to the target language by enhancing their motivation and curiosity towards the subjects taught as well as by contributing to reduce their classroom anxiety thus resulting in a thriving learning community.